The pathogenicity island encoded PvrSR/RcsCB regulatory network controls biofilm formation and dispersal in Pseudomonas aeruginosa PA14 - Mikkelsen,H; Hui,K; Barraud,N; Filloux,A (Molecular Microbiology, 2013)
Pseudomonas aeruginosa biofilm formation is linked to persistent infections in humans. Biofilm formation is facilitated by extracellular appendages, some of which are assembled by the Chaperone Usher Pathway (Cup). The cupD gene cluster is located on the PAPI1 pathogenicity island of strain PA14 and has probably been acquired together with four genes encoding twocomponent signal transduction proteins. We have previously showed that the RcsB response regulator activates expression of the cupD genes, which leads to the production of CupD fimbriae and increased attachment. Here we show that RcsB activity is tightly modulated by two sensors, RcsC and PvrS. While PvrS acts as a kinase that enhances RcsB activity, RcsC has a dual function, first as a phosphorelay, and second as a phosphatase. We found that, under certain growth conditions, overexpression of RcsB readily induces biofilm dispersal. Microarray analysis shows that RcsB positively controls expression of pvrR that encodes the phosphodiesterase required for this dispersal process. Finally, in addition to the PAPI1 encoded cupD genes, RcsB controls several genes on the core genome, some of which encode orphan response regulators. We thus discovered that RcsB is central to a large regulatory network that finetunes the switch between biofilm formation and dispersal.